2001
DOI: 10.1034/j.1600-065x.2001.1820102.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic tolerance maintained by CD25+ CD4+ regulatory T cells: their common role in controlling autoimmunity, tumor immunity, and transplantation tolerance

Abstract: There is accumulating evidence that T-cell-mediated dominant control of self-reactive T-cells contributes to the maintenance of immunologic self-tolerance and its alteration can cause autoimmune disease. Efforts to delineate such a regulatory T-cell population have revealed that CD25+ cells in the CD4+ population in normal naive animals bear the ability to prevent autoimmune disease in vivo and, upon antigenic stimulation, suppress the activation/proliferation of other T cells in vitro. The CD25+ CD4+ regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
1,015
4
27

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,373 publications
(1,082 citation statements)
references
References 2 publications
28
1,015
4
27
Order By: Relevance
“…Second, the decrease in CD25ϩ lymphocytes in this population is consistent with a decrease in regulatory T cells that may lead to increased susceptibility to autoimmune phenomena, although this is speculative. CD25 is generally known as a marker of the IL-2 receptor on T lymphocytes and functions as a marker of regulatory or suppressor T cells (17,18). However, CD25 is not only a marker for regulatory T cells, but is also transiently upregulated on activated nonregulatory T cells independently stimulated by CD69 (19).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the decrease in CD25ϩ lymphocytes in this population is consistent with a decrease in regulatory T cells that may lead to increased susceptibility to autoimmune phenomena, although this is speculative. CD25 is generally known as a marker of the IL-2 receptor on T lymphocytes and functions as a marker of regulatory or suppressor T cells (17,18). However, CD25 is not only a marker for regulatory T cells, but is also transiently upregulated on activated nonregulatory T cells independently stimulated by CD69 (19).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Many studies have focused on the removal of Tregs in animal models, resulting in the improved function of CD4 1 effector T cells (Teff cells) and the enhancement of the antitumor response. 9 These observations suggest that the success of immunotherapy for cancer may ultimately depend on the balance between Treg and Teff cells. 10,11 Increasing evidence indicates that Tregs mediate immunosuppressive functions through the utilization of many soluble mediators and cell-to-cell contact, further inducing a positive feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…Surh et al proposed that homeostatic T cell proliferation may be due to increased accessibility to stimulatory factors or relieved "T cell congestion", which would liberate T cells from constant inhibitory cues from cellcell interactions [23]. Several recent studies have demonstrated that depletion of CD4 + CD25 + regulatory T cells augmented priming of tumor-specific T cells in vaccinated mice [24][25][26][27][28]. Although depletion of CD4 + CD25 + regulatory T cells did not affect lymphopenia-driven proliferation of naive T cells, tumor vaccine-driven proliferation of antigen-specific T cells in lymphopenic hosts may be amplified by the depletion.…”
Section: Discussionmentioning
confidence: 99%